Targeting mitochondria with natural polyphenols for treating Neurodegenerative Diseases: a comprehensive scoping review from oxidative stress perspective - Yueyue Guan; Lei Li; Rui Yang; Yun Lu; Jun Tang (Journal of Translational Medicine)
Abstract Neurodegenerative diseases are a class of conditions with widespread detrimental impacts, currently lacking effective therapeutic drugs. Recent studies have identified mitochondrial dysfunction and the resultant oxidative stress as crucial contributors to the pathogenesis of neurodegenerative diseases. Polyphenols, naturally occurring compounds with inherent antioxidant properties, have demonstrated the potential to target mitochondria and mitigate oxidative stress. This therapeutic potential has garnered significant attention in recent years. Investigating the mitochondrial targeting capacity of polyphenols, their role in functional regulation, and their ability to modulate oxidative stress, along with exploring novel technologies and strategies for modifying polyphenol compounds and their formulations, holds promise for providing new avenues for the treatment of neurodegenerative diseases.